Developing a meaningful language education policy for Caribbean States - Robertson, Ian E. (My University, 1992)
This paper examines the factors responsible for the pattern of language education that exists in the former British colonies, where the teaching and learning of languages continue to be completely instrumentally oriented. This involves the rejection of the Creole languages as having any status other than that of a bastardized form of the relevant European lexical donor language. This paper attempts to begin the type of discussion that could encourage the rethinking considered necessary. It makes a case for a more comprehensive look at language education from and education perspective, and for using the goals of education to determine the guiding principles for language education policy.
2nd Biennial Cross-Campus Conference on Education, St. Augustine, Trinidad 22-24 Apr, 1992
Keywords: language education; Caribbean states